1991
DOI: 10.1302/0301-620x.73b5.1894669
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional collagen architecture in bovine articular cartilage

Abstract: The three-dimensional architecture of bovine articular cartilage collagen and its relationship to split lines has been studied with scanning electron microscopy. In the middle and superficial zones, collagen was organised in a layered or leaf-like manner. The orientation was vertical in the intermediate zone, curving

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
185
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(197 citation statements)
references
References 16 publications
12
185
0
Order By: Relevance
“…21(d) and (h)]. The orientation of the collagen fibers can be deduced from measurement of the quadrupolar splitting at two orientation of the plug relative to the field according to eqn (3). This indicates the gradual ordering of the collagen fibers during growth, in agreement with biomechanical and EM results obtained for the maturation of rat articular cartilage (69,70).…”
Section: Study Of the Maturation Of Pig Articular Cartilagesupporting
confidence: 76%
See 1 more Smart Citation
“…21(d) and (h)]. The orientation of the collagen fibers can be deduced from measurement of the quadrupolar splitting at two orientation of the plug relative to the field according to eqn (3). This indicates the gradual ordering of the collagen fibers during growth, in agreement with biomechanical and EM results obtained for the maturation of rat articular cartilage (69,70).…”
Section: Study Of the Maturation Of Pig Articular Cartilagesupporting
confidence: 76%
“…Articular cartilage can be divided into four zones, which differ in the relative amounts of cartilage constituents and in the collagen fiber orientation: the calcified zone, the radial zone, the intermediate zone and the superficial zone. Collagen fibers rise vertically from the bone and keep the same orientation throughout the calcified and radial zones (2)(3)(4). In the intermediate zone, the fibers bend and then flatten in the superficial zone, where they are aligned parallel to the cartilage surface.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, highresolution SEM imaging and cryofracture techniques have suggested that this model be revised. The work of Clark 11 and Jeffrey et al 12 suggest a model shown schematically in Figure 2, in which fibers arising from the subchondral bone form well-defined sheets or lamellae which curve over in the "transitional" layer to then lie parallel to the surface in the most superficial tangential layer. In this model the fibers do not descend back to the bone but terminate in the tangential layer.…”
Section: Cartilage Structurementioning
confidence: 99%
“…While the juvenile cartilage shows six-laminar structuring (lower region of the anterior horn), the adult cartilage appears bilaminar under the given measurements conditions bilaminar appearance the cartilage shows a surface zone of high intensity and a broad zone with decreasing intensity from the surface to the bone. These appearances were interpreted as MR visualization of the arcade [or leaf-like (25,26)] model of the hyaline cartilage. Figure 4(a) documents that the MR visualized multilaminarity can be influenced by the adjacent tissue.…”
Section: Age-dependence Of Collageneous Networkmentioning
confidence: 99%